Nature and liberty - Zvesper, John, 1948- (Routledge, 1993)
Liberal democracy, it has been claimed, stands at the end of history. But there are hidden internal strains that could threaten its fabric. Nature and Liberty explores three of the most important practical problems of modern liberal politics - those connected with ethnicity and race, sex and the family, and bureaucratized government. The author traces liberals' difficulties in dealing with these problems to their own reluctance to have recourse to nature as a guide for political life.